Edukasi Pemberian Senam Otak untuk Mencegah Demensia pada Lansia di Posyandu Kenanga Waru - Amalia Prasetyaningtyas; Isnaini Herawati; Annisa Amaliah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
When someone enters old age, symptoms such as senility or difficulty remembering new information often appear. This condition is known as dementia, a syndrome characterized by decreased cognitive function, behavioral changes, memory impairment, disorientation, and difficulty communicating and making decisions. This community service program aims to provide information and understanding about how to handle dementia that can be done at home. Activities are carried out through a counseling method consisting of a pre-test, education, and post-test, using leaflets and questionnaires containing questions to measure the level of understanding of participants. The results of the counseling showed an increase in participant knowledge, as seen from the comparison of the graph between the pre-test and post-test results. Education accompanied by brain gymnastics practices has been shown to have a positive impact on increasing participants' understanding of dementia and how to handle it. It is hoped that this counseling will continue to provide benefits to participants and can be applied in everyday life.